Requirement for an intact T-cell actin and tubulin cytoskeleton for efficient assembly and spread of human immunodeficiency virus type 1. - Jolly, C; Mitar, I; Sattentau, Q (2007)
Human immunodeficiency virus type 1 (HIV-1) infection of CD4(+) T cells leads to the production of new virions that assemble at the plasma membrane. Gag and Env accumulate in the context of lipid rafts at the inner and outer leaflets of the plasma membrane, respectively, forming polarized domains from which HIV-1 buds. HIV-1 budding can result in either release of cell-free virions or direct cell-cell spread via a virological synapse (VS). The recruitment of Gag and Env to these plasma membrane caps in T cells is poorly understood but may require elements of the T-cell secretory apparatus coordinated by the cytoskeleton. Using fixed-cell immunofluorescence labeling and confocal microscopy, we observed a high percentage of HIV-1-infected T cells with polarized Env and Gag in capped, lipid raft-like assembly domains. Treatment of infected T cells with inhibitors of actin or tubulin remodeling disrupted Gag and Env compartmentalization within the polarized raft-like domains. Depolymerization of the actin cytoskeleton reduced Gag release and viral infectivity, and actin and tubulin inhibitors reduced Env incorporation into virions. Live- and fixed-cell confocal imaging and assay of de novo DNA synthesis by real-time PCR allowed quantification of HIV-1 cell-cell transfer. Inhibition of actin and tubulin remodeling in infected cells interfered with cell-cell spread across a VS and reduced new viral DNA synthesis. Based on these data, we propose that HIV-1 requires both actin and tubulin components of the T-cell cytoskeleton to direct its assembly and budding and to elaborate a functional VS.